A time-reversal suboptimal detector for underwater acoustic barriers - Jesus, S. M. (2008)
This paper proposes an experimental setup composed of two interconnected vertical arrays: one transmit only array (TOA) and a receive only array (ROA). It is shown that using the time reversal principle, where the ocean is used as a spatial matched filter, signal energy can be simultaneously focused on each ROA hydrophone and thus obtain the detector output by simple summation of the received energy over the array. This setup effectively configures a multistatic system with several transmitters and several receivers coherently processed both in time and space. Simulations using a ray trace propagation model combined with a naive scattering formulation show that the obtained empirical detection probability is close to the theoretical optimal bound derived assuming space - time white Gaussian noise. This system was tested in a sea trial that took place during September 2007 in the Hopav°agen Bay near Trondheim, Norway. The actual setup was composed of a 2 sources TOA on a shallow area of 8 m depth near the shore and a 16 receivers ROA approximately 100 m apart in a 8 to 25 m depth range dependent duct. The transmitted signals were 200 ms duration LFMs with 3 kHz bandwidths in two frequency bands centered on 5 and 10 kHz. The results obtained in realistic conditions show that a 1.7 m2 hard plate could be detected when placed across the barrier. Several results are presented and compared with the theoretical values. Although the system can be significantely improved, in particular by using more populated source and receiving arrays, it is believed that these results can be reproduced at sea in harbor like conditions.